Impact of the characteristics of the flow regimes and dynamics of coarse particles fly ash in circular transportation based on CFD-DEM - Yanuar; Raja Fatah Satrio Abimanyu; Gunawan; Sri Poernomo Sari; Chakra Merdeka (BKS-TM Indonesia, 2025)
Fly ash are the primary residues generated from coal combustion, and they represent a serious environmental concern due to their volume and handling complexity. One potential mitigation strategy involves transporting these materials in the form of slurry through pipelines; however, achieving efficient flow remains a significant challenge due to the high concentration of solid particles. This study investigates the energy demands of fly ash slurry flow within circular pipelines using a combined approach of experimental observation and Computational Fluid Dynamics (CFD) simulation. Slurry concentrations of 30%, 40%, and 50% by weight were evaluated. Key flow parameters analyzed include shear stress, shear rate, Reynolds number, and friction factor. The Turbulent Kinetic Energy (TKE) [Figure (c)] shows a clear escalation in kinetic energy with increasing concentration. FA 50% attains the highest kinetic energy (0.0863673), almost twice that of FA 40% (0.0561258) and quadruple that of FA 30% (0.0185431). The CFD simulation results were validated against experimental data, showing a margin of error 6.212%, 4.163%, 5.032[1]% for 30%, 40%, 50% fly ash, and 5.51460%, 8.79267%, 2.72044% for 30%, 40%, 50% bottom ash, respectively, supported by a good Grid Convergence Index of 0.017432% which indicates strong agreement. These findings offer a technical basis for developing energy efficient slurry transport systems and provide further insight into the non-Newtonian behavior characteristic of high solids flow regimes.